Association of the Three Common SNPs of Cyclooxygenase-2 Gene (rs20417, rs689466, and rs5275) with the Susceptibility of Breast Cancer: An Updated Meta-Analysis Involving 34,590 Subjects - Dai, Zhi-Jun (Hindawi Publishing Corporation, 2014)
Several single nucleotide polymorphisms have been identified in cyclooxygenase-2 (COX-2) genes (e.g., −765 G>C (rs20417), −1195G>A (rs689466), and 8473 C>T (rs5275)). The association of these SNPs with the risk of different cancer types is still controversial. This study aims to evaluate the correlation between these SNPs and breast cancer risk in different ethnic groups. We have searched PubMed, Web of Knowledge, and Embase for relevant studies. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to estimate the strength of the associations. A total of 13 studies (15,330 cases and 19,260 controls) were eligible for meta-analysis. This meta-analysis showed that COX-2 rs20417 polymorphism was correlated with an increased risk of breast cancer in Caucasians, while rs689466 was associated with a decreased risk of breast cancer in Caucasians. The rs5275 polymorphism had no association with breast cancer risk.